2017
DOI: 10.1111/jeu.12434
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Phylogenetic Analyses of Three Novel Naegleria Isolated from Freshwaters on Jeju Island, Korea, During the Winter Period

Abstract: The genus Naegleria is one of the best known heterolobosean groups, and is the causative agent of primary amoebic meningoencephalitis. This group is rarely studied in temperate regions during winter. Here, three novel Naegleria were isolated from freshwaters on Jeju Island, Korea, during winter. Two isolates were amoeboflagellates, and one of the three amoebae did not undergo enflagellation. All amoebae had eruptive pseudopodia, and the layer of refractile granules around a large nucleus. They formed a cyst wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Heterolobosea are typically found in soil, freshwater, and marine environments, as well as in extreme habitats (Harding and Simpson ; Khwon and Park ; Pánek et al. , ; Park ; Tyml et al.…”
Section: Discussionmentioning
confidence: 99%
“…Heterolobosea are typically found in soil, freshwater, and marine environments, as well as in extreme habitats (Harding and Simpson ; Khwon and Park ; Pánek et al. , ; Park ; Tyml et al.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the species inventory of other halophilic/halotolerant groups in Heterolobosea was further expanded. Several OTUs related to typical freshwater or marine heterolobosean species (e.g., Naegleria and Heteramoeba ) were recovered from high-salinity waters, and they may form cysts to remain viable [ 18 , 81 , 82 ]. Similar to our results, Post et al [ 74 ] reported that Neagleria spp.…”
Section: Discussionmentioning
confidence: 99%
“…The experiment was performed on cultures of 'ES010' incubated at 50, 100, and 150 PSU for 7 days. In addition, the freshwater species Naegleria neojejuensis was used as a negative control (Khwon and Park, 2018). The cells were concentrated by centrifugation at 5,000 × g for 30 min.…”
Section: Intracellular Ion Accumulation Assaymentioning
confidence: 99%
“…The length of the cytostome in the flagellate phase of Pharyngomonas (>9 μm) longer than that in E. salpumilio, whereas Willaertia has cytostome (Patterson et al, 2000;Park and Simpson, 2011). Naegleria flagellates have two flagella, but lack a cytostome (Khwon and Park, 2018). Tulamoeba is isolated from hypersaline environments and has two flagella, but the flagellates show an elongated shape (Kirby et al, 2015) rather than the spherical shape of E. salpumilio.…”
Section: Taxonomic Assignmentmentioning
confidence: 99%
See 1 more Smart Citation